Distinct Gene Expression Patterns of Two Heat Shock Protein 70 Members During Development, Diapause, and Temperature Stress in the Freshwater Crustacean Daphnia magna - Chen, Luxi; Gómez, Rocío; Weiss, Linda C. (Frontiers in Cell and Developmental Biology, 2021)
Dormancy is a lifecycle-delay that allows organisms to escape suboptimal environmental conditions. As a genetically programmed type of dormancy, diapause is usually accompanied by metabolic depression and enhanced tolerance towards adverse environmental factors. However, the drivers and regulators that steer an organism’s development into a state of suspended animation to sustain environmental stress, have not been fully uncovered. Heat shock proteins 70 (HSP70s), which are often produced in response to various types of stress, have been suggested to play a role in diapause. Considering the diversity of Hsp70 family gene products, different Hsp70 isoforms may have different functions during diapause. In the present study, we demonstrate gene expression of two Hsp70 isoforms (isoform A and B together with protein localization of B) throughout continuous and diapause interrupted development of Daphnia magna. Before and after diapause the expression Dmhsp70-A is low. Only shortly before diapause and during diapause, this isoform is significantly upregulated and may therefore be involved in diapause preparation and maintenance. In contrast, Dmhsp70-B is expressed only in developing embryos but not in diapausing embryos. During continuous development, the protein of this isoform is localized in the cytosol where it could drive e.g. cell cycle progression. When we expose both embryo types to heat stress, expression of both isoforms increase only in developing embryos and the protein of isoform B is translocated to the nucleus. In this stress-formation, this protein provides effective protection of nucleoplasmic DNA. As we also see this localization in diapausing embryos, it appears that Daphnia embryo types share a common subcellular strategy when facing dormancy or heat shock, i.e. they protect their DNA by HSP70B nuclear translocation. Our study underlines the distinctive role different HSP70 family members play throughout continuous and diapause interrupted development.